2007
DOI: 10.1007/s11418-007-0212-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Oldenlandia corymbosa L. of Thai origin

Abstract: From the whole plants of Oldenlandia corymbosa of Thai origin, ten compounds have been isolated and elucidated as geniposide, 6 alpha-hydroxygeniposide, scandoside methyl ester (6 beta-hydroxygeniposide), asperulosidic acid, deacetylasperuloside, asperuloside, 10-O-benzoylscandoside methyl ester, 10-O-p-hydroxybenzoylscandoside methyl ester, (+)-lyoniresinol-3 alpha-O-beta-glucopyranoside, and rutin. Their structures were determined on the basis of spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…By searching the known iridoid glucosides with an MW of 371 in P . scanddens and by comparing the chromatographic behavior with published data, the compound corresponding to peak 6 was tentatively identified as deacetyl asperuloside (Suomi et al ., ; Noiarsa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…By searching the known iridoid glucosides with an MW of 371 in P . scanddens and by comparing the chromatographic behavior with published data, the compound corresponding to peak 6 was tentatively identified as deacetyl asperuloside (Suomi et al ., ; Noiarsa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…It is reported to possess antioxidant [ 4 , 5 ], anti-inflammatory [ 6 ], hepatoprotective [ 7 , 8 ], antitumor [ 9 , 10 ], antimalarial [ 11 ] and anti-nociceptive [ 12 ] activities. Iridoids, carboxylic acids, flavonoids, phenolics and their derivatives, triterpenes, anthranquinones and coumarins were isolated from HC [ 13 , 14 , 15 ]. Iridoid glycosides were reported as the main constituents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hedyotis corymbosa L. or Rumput Mutiara is one of natural resources which revealed to perform several anticancer properties (Sivapraksam, et al, 2014). Based on phytochemical studies on Hedyotis corymbosa L., several flavonoids, terpenoids, and glycosides were present, such as ursolic acid, oleanolic acid, and gamma sitosterol (Noiarsa, et al, 2008). extract, Previous study reported that Hedyotis corymbosa L. ethanolic extract showed significant anticancer activity on K562 human leukemia cell lines (Pandey, et al, 2012) and on WiDr colon cancer (Meiftasari, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%